Upaya Peningkatan Mahasiswa Baru Melalui Sosialisasi dan Promosi Universitas Timor - Fredirikus Timo; Rikhardus Bria Seran; Emilia Khristina Kiha; Anggelina Delviana Klau (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Higher education is said to be of quality if the learning process takes place effectively and students gain experiences that are meaningful to themselves and beneficial to society and national development. The educational units that provide higher education are universities, one of which is the University of Timor. Every year, the University of Timor always searches for students through new student admissions which are carried out with socialization and promotional activities. This activity was carried out as a form of effort by the University of Timor to be able to provide information regarding new student admissions and to socialize a positive image to attract students' attention about the University of Timor. Socialization and promotional activities are carried out in the form of lectures, discussions and questions and answers. This activity was carried out at SMAN 1 East Tasifeto. The results of this activity went well and were able to increase students' interest in continuing higher education at the University of Timor as seen from their enthusiasm in asking further questions about how to register.